(untitled) (Research, Society and Development, 2019)
The present study aims to analyze some perceptions and suggestions of the academics regarding the application of these methodologies in a Physiotherapy course. The first two levels of the Kirkpatrick model were used, applying devices such as self-assessment questionnaires. The sample consisted of 83 college students. It was concluded that the application of active teaching-learning methodologies facilitates group work and attends to students’ expectations of learning about the subject, however, it is necessary to adapt some steps, especially the strategy so that there is no doubt for students in the end of the process.